Influence of the educational factors in projects of investigator in the faculty of law – UNHEVAL - Nájar-Farro, César A. (2019)
The present study examined how the pedagogical factors related to learning influence in the development of research projects done by the students of the Faculty of Law and Political Sciences of Hermilio Valdizán National University. For this purpose an interview administered to students, evaluated by university professors specialists in scientific research of our environment was used. The main components of the socio legal research process that is set to the undergraduate students were also reviewed. The analyzed data suggest that the pedagogical factors involved and some applied by university professors suffer from differences and deficiencies during its materialization; noting that it affects students, and henee in the negative result of the limited production of scientific research projects. It was described the opérate strategies: the reflection and the recognition of sources of existing support necessary to facilitate and improve the pedagogical factors related to learning that influence positively on the development of a research project.